Tephra From the 3 March 2015 Sustained Column Related to Explosive Lava Fountain Activity at Volcán Villarrica (Chile) - Romero, Jorge E.; Vera, Franco; Polacci, Margherita; Morgavi, Daniele; Arzilli, Fabio; Alam, Mohammad Ayaz; Bustillos, Jorge E.; Guevara, Alicia; Johnson, Jeffrey B.; Palma, José L.; Burton, Mike; Cuenca, Evelyn; et al. (Frontiers in Earth Science, 2018)
Villarrica Volcano in the Southern Andes of Chile has sustained persistent open conduit activity, associated with a dynamic lava lake since at least 1984-85. Increased seismic activity and degassing in August 2014 was followed by increased Strombolian activity starting in February 2015 and culminated with a 1.5 km-high lava fountain on 3 March 2015. This eruption produced tephra fallout, spatter agglutination, clastogenic lavas and mixed avalanche deposits. Field work carried out in 2017 and 2018 focused upon the tephra fallout deposits from the 3 March 2015 paroxysmal eruption. Tephra fall deposits produced by lava fountain and a rapid transition to sustained eruption column at Villarrica are here described for first time. Tephra dispersion was observed mostly southeast of the crater in a narrow, elongated, nearly-elliptic area. Minimum observed tephra loading was estimated to be 80-120 g/m2 at crosswind locations, while maximum load estimation was about 11,500 g/m2, at 7-9 km distance from the vent. At 6-8 km downwind, the tephra fall deposit consisted of a single black scoria layer, fall varied from a lapilli blanket at medial distances (9-19 km) to a few individual particles at distal sites (20-43 km). All samples are vitrophyric in texture, with a mineral assemblage of plagioclase (3-30 %), clinopyroxene (2-5 %), olivine (1-4 %) and scarce orthopyroxene (<1 %) phenocrysts. We estimate that 1.4 x 109 kg, equivalent to ~2.4 x 106 m3 of basaltic andesite tephra (52.8 to 54.7 SiO2 wt. %), were erupted within a period of about 16 minutes at a mass eruption rate of ~1.5 x 106 kg/s. The sustained eruption column height was estimated at ~10.8 km, with magnitude and intensity of 2.11 and 9.13 respectively. We propose that a rejuvenated, volatile-rich magmatic intrusion is the probable triggering factor for the paroxysm. The Villarrica eruption is classified as a short-lived, large-scale lava fountain, similar to intense historical lava fountains at Mt. Etna and Kilauea. As evident by devastating 20th century Villarrica eruptions which also developed similar lava fountain behavior, this eruption style should be considered as frequent and a potential source of volcanic hazard in the future.